2015
DOI: 10.1016/j.cogpsych.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Infants understand deceptive intentions to implant false beliefs about identity: New evidence for early mentalistic reasoning

Abstract: Are infants capable of representing false beliefs, as the mentalistic account of early psychological reasoning suggests, or are they incapable of doing so, as the minimalist account suggests? The present research sought to shed light on this debate by testing the minimalist claim that a signature limit of early psychological reasoning is a specific inability to understand false beliefs about identity: because of their limited representational capabilities, infants should be unable to make sense of situations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 66 publications
3
68
0
3
Order By: Relevance
“…First, they confirm prior findings that by the second year of life, infants can attribute false beliefs to agents (e.g., Buttelmann et al, 2009;Kovács et al, 2010;Luo, 2011;Onishi & Baillargeon, 2005;Scott et al, 2015;Senju et al, 2011;Träuble et al, 2010). Second, these results extend these findings to a novel belief-based response: infants can reason not only about which location a mistaken agent will act on, but also about how her false belief will affect her subsequent emotional displays.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…First, they confirm prior findings that by the second year of life, infants can attribute false beliefs to agents (e.g., Buttelmann et al, 2009;Kovács et al, 2010;Luo, 2011;Onishi & Baillargeon, 2005;Scott et al, 2015;Senju et al, 2011;Träuble et al, 2010). Second, these results extend these findings to a novel belief-based response: infants can reason not only about which location a mistaken agent will act on, but also about how her false belief will affect her subsequent emotional displays.…”
Section: Discussionsupporting
confidence: 83%
“…Rather, the present study adds to a growing body of evidence that infants can reason about causal interactions amongst mental states (e.g., Scott & Baillargeon, 2009;Scott et al, 2015). As such evidence accumulates, the existence of arbitrary limits on infants' false-belief understanding become less plausible.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…By the same token, our results also cast doubt on the view that a fundamental change in children's false-belief understanding takes place around age 4 y and makes possible success at these tasks. When processing demands are sufficiently reduced, even 2.5-y-olds succeed at a traditional task, suggesting that a single psychological-reasoning system, capable of attributing counterfactual states as well as motivational and epistemic states, exists from infancy onward (1,31,52,53).…”
Section: Significancementioning
confidence: 99%
“…Since 2005, over two dozen published studies have reported evidence of falsebelief understanding in children between 6 months and 3 years of age (for a review, see Baillargeon et al, 2015). These subsequent studies have addressed two important, interrelated questions regarding the origins and development of false-belief understanding.…”
mentioning
confidence: 99%